전방십자인대 파열 수술 중 발생한 폐동맥혈전색전증의 응급체외순환을 이용한 치료 - 장동민; Dong Min Jang; 김경태; Kyung Tae Kim; 김정원; Jung Won Kim; 최원주; Won Joo Choe; 이정락; Jeong Rak Lee; 이상일; Sang Il Lee (Korean journal of anesthesiology, 2007)
A 56 year old female patient was transferred to the operating room for the repair of anterior cruciate ligament under general anesthesia. Initial vital sign was stable, but there was gradual decreases of the blood pressure and end-tidal CO2 after femur tourniquet application. We suspected the pulmonary thromboembolism, and started massive treatment of using ventilator with 100% O2, various invasive monitors and many vasopressors. Because the patient's vital sign was so unstable, we finally made a decision of using emergency bypass system (Capiox EBS, Terumo, Japan) by femoral artery and vein. After that, we transferred the patient to intensive care unit, and continued vigorous treatment. The patient was diagnosed as pulmonary thromboembolism by CT scan. We treated her with infusion of heparin and maintained ACT above 200 second. The 4th day at the intensive care unit, we removed the emergency bypass system. We transferred her to general ward without any complication after 12th day postoperatively. KCI Citation Count: 0